Local Wisdom-based Character Values in Millennial Madurese Community: A Study of Molothen Traditions - Wahab; Khairiansyah, Heri; Misridah (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
Molothen (Mawlid al-Nabi) for the people of Madura is a profoundly ingrained local culture and wisdom. Apart from being full of religious values, this tradition also has character education values. This study aims to determine the values of character education in the Molothen tradition and how this shapes the millennial Madurese community's character. This article is a case study research using a qualitative approach. Data were collected using observation, interview, and documentation techniques. The results showed that the Madurese one generation performed the Molothen tradition to another. The character values contained in the Molothen tradition are religion, discipline, independence, responsibility, and cooperation/solidarity. These character values can then shape the personality of the millennial Madurese community to become virtuous.